138k views
3 votes
Evaluate 3x^3y-2/5x^-2y^3 for x=2 and y=3

32/405
160/81
2/5

User Mbr
by
6.2k points

1 Answer

1 vote

The given expression is


(3x^3 y^(-2))/(5x^(-2) y^3)

Given values of x and y are x=2 and y=3

And on substituting these values, we will get


(3(2)^3 (3)^(-2))/(5(2)^(-2) (3)^3)

Here we need to convert negative exponents to positive exponent, and for that we need to flip the term with negative exponent .


(3*2^3*2^2)/(5*3^2*3^3)


(2^5)/(5*3^4)=(32)/(405)

So the correct option is the first option .

User JonahGabriel
by
6.0k points